Type I PRMT Inhibition Protects Against C9ORF72 Arginine-Rich Dipeptide Repeat Toxicity - Premasiri, Alan S.; Gill, Anna L.; Vieira, Fernando G. (Frontiers in Pharmacology, 2020)
Repeat expansion mutations in the C9ORF72 gene are the most common genetic cause of amyotrophic lateral sclerosis (ALS) and (FTD). Repeat-associated non-AUG translation of this expansion produces dipeptide repeat proteins (DRPs). The arginine containing DRPs, polyGR and polyPR, are consistently reported to be the most toxic. Here we demonstrated that small molecule inhibition of Type I protein arginine methyltransferases protects against polyGR and polyPR toxicity. Furthermore, our findings suggest that asymmetric dimethylation of polyGR and polyPR by Type I PRMTs play important roles in their cytotoxicity.